1979
DOI: 10.2337/diab.28.5.457
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline: Potentiation of Arginine-induced Somatostatin Release from the Isolated Rat Pancreas

Abstract: Somatostatin's release from the isolated rat pancreas was studied using a perfusion technique. Arginine at a concentration of 19 mM produced a biphasic increase in somatostatin release from the perfused rat pancreas. Both first and second phases of somatostatin's increase are significantly higher in the presence of 1 mM theophylline than in the absence of the drug. These results indicate the possible inclusion of the adenylate cyclase--cyclic AMP system in the regulatory mechanism of rat pancreatic somatostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Pancreases and attached segments of duodenum from overnight fasted male Sprague Dawley rats weighing 300-350 g, were perfused in situ by a previously described method [6]. All perfusions were.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pancreases and attached segments of duodenum from overnight fasted male Sprague Dawley rats weighing 300-350 g, were perfused in situ by a previously described method [6]. All perfusions were.…”
Section: Methodsmentioning
confidence: 99%
“…Streptozotocin treatment 90 rain prior to the onset of perfusion resulted in changes in somatostatin, glucagon, and insulin responses to glucose and arginine similar to those of alloxan. The present results are consistent with an effect of alloxan and streptozotocin on the D cell similar to that on the B cell, namely, interference with a glucose-mediated effect on hormone secretion.Key words: Alloxan, perfusion, theophylline, streptozotocin, somatostatin, insulin, glucagon, rat, glucose, pancreas, arginine.Somatostatin is localized within the pancreas in secretory granules in D cells of the islets of Langerhans [1, 2] and its secretion is enhanced by glucose [3,4], theophylline [5,6], and glucagon [7]. Administration of exogenous somatostatin inhibits the release of insulin and glucagon [8,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The release of pancreatic IRS from the isolated perfused rat pancreas [39], rat pancreatic islets [86], and monolayer cell cultures of embryonic chicken pancreas [8], is also aug mented by addition of theophylline to the perfusate or incu bation medium. Theophylline, which results in a rise of cAMP due to inhibition of phosphodiesterase, significantly enhances the stimulatory effects of high glucose levels on insulin and IRS secretion.…”
Section: Effects Of Ca++ and Camp On Somatostatin Release From Gep Ormentioning
confidence: 99%
“…Goto et al (1979) reported that somatostatin, glucagon and insulin release were significantly higher in the presence of 1 mM theophylline with 19 mM arginine than 19 mM arginine only from the isolated rat pancreas.…”
Section: Discussionmentioning
confidence: 96%